Milk phospholipids protect Bifidobacterium longum subsp. infantis during in vitro digestion and enhance polysaccharide production - Kosmerl, Erica; González-Orozco, Brianda D.; García-Cano, Israel; Ortega-Anaya, Joana; Jiménez-Flores, Rafael (Frontiers in Nutrition, 2023)
Bifidobacterium longum subsp. infantis is associated with the gut microbiota of breast-fed infants. B. infantis promotes intestinal barrier and immune function through several proposed mechanisms, including interactions between their surface polysaccharides, the host, and other gut microorganisms. Dairy foods and ingredients are some of the most conspicuous food-based niches for this species and may provide benefits for their delivery and efficacy in the gut. Milk phospholipid (MPL)-rich ingredients have been increasingly recognized for their versatile benefits to health, including interactions with the gut microbiota and intestinal cells. Therefore, our objective was to investigate the capacity for MPL to promote survival of B. infantis during simulated digestion and to modulate bacterial polysaccharide production. To achieve these aims, B. infantis was incubated with or without 0.5% MPL in de Man, Rogosa, and Sharpe (MRS) media at 37 °C under anaerobiosis. Survival across the oral, gastric, and intestinal phases using in vitro digestion was measured using plate count, along with adhesion to goblet-like intestinal cells. MPL increased B. infantis survival at the end of the intestinal phase by at least 7% and decreased adhesion to intestinal cells. The bacterial surface characteristics, which may contribute to these effects, were assessed by ζ-potential, changes in surface proteins using comparative proteomics, and production of bound polysaccharides. MPL decreased the surface charge of the bifidobacteria from -17 to -24 mV and increased a 50 kDa protein (3-fold) that appears to be involved in protection from stress. The production of bound polysaccharides was measured using FTIR, HPLC, and TEM imaging. These techniques all suggest an increase in bound polysaccharide production at least 1.7-fold in the presence of MPL. Our results show that MPL treatment increases B. infantis survival during simulated digestion, induces a stress resistance surface protein, and yields greater bound polysaccharide production, suggesting its use as a functional ingredient to enhance probiotic and postbiotic effects.